Strategies Considered Effective for Transforming Business Education Programmes to the Needs of 21st Century Workplace in Delta State, Nigeria - Nwazor, J. C.; Oghenekaro, Onokpanu Michel (African Journal of Education and Practice, 2016)
Purpose: The study was conducted to identify the strategies considered effective for transforming business education programmes to the needs of the 21st century workplace. Methodology: One research question and two hypotheses guided the study. A survey research design was adopted for the study. The population consisted of 122 business education lecturers in tertiary institutions in Delta state. A 17-item questionnaire was used. Mean and standard deviation and z-test were used in the analysis of data. Findings: The study revealed that all the 17-item statements on the strategies for transforming business education programmme to the needs of the 21st century workplace were considered effective. Conclusion and policy recommendations: The study concluded that unless these effective strategies are adopted business education will have little capacity to adequately develop Nigerian graduates of business education to meet the challenges and complexities of the 21st century workplace. The study recommended among others that a closer collaboration between academicians of business education and business executives should be implemented continually in order to help students acquire the necessary 21st century workplace competencies while in school.